Role of Balinese Flute Playing in Enhancing Cognitive Function and Serum Brain-derived Neurotrophic Factor (BDNF) Levels in the Elderly - Anak Agung Ayu Putri Laksmidewi; Ni Putu Ayu Putri Mahadewi; Lasta Arshinta; Made Sebastian Dwi Putra Hardika; Christine Kathy Putri Sari (Diponegoro International Medical Journal, 2025)
Background: Aging is associated with cognitive decline, yet the brain retains adaptive capacity with proper stimulation. Musical activities, including traditional Balinese flute playing, have shown potential in enhancing memory, concentration, and cognitive performance.Objective: This study examined the effect of playing the Balinese flute piece “Morning Happiness” on cognitive improvement in the elderly, as indicated by changes in serum Brain-derived Neurotrophic Factor (BDNF) levels.Methods: This experimental study was conducted from June to September 2024 among elderly participants (>60 years) with controlled risk factors. Subjects were randomized into an intervention group (n=28) and control group (n=14), with a male-to-female ratio of 3:4. The intervention group played the Balinese flute for 20 minutes daily, while the control group listened to the same music for 10 minutes, three times weekly. Cognitive function was assessed using the Indonesian version of the Montreal Cognitive Assessment (MoCA-Ina), and serum BDNF levels were measured before and after the intervention.Results: The intervention group showed a significant improvement in total MoCA-Ina scores (Z = -2.82, p = 0.005), particularly in abstraction (Z = -2.296, p = 0.022) and delayed recall (Z = -3.436, p = 0.026). Serum BDNF levels also increased significantly after the intervention (from 5.46 ± 6.16 to 7.63 ± 10.16; p = 0.033), while no significant changes were observed in the control group.Conclusion: Balinese flute playing enhances cognitive function, especially abstraction and memory recall, and increases serum BDNF, supporting its role as a non-pharmacological strategy to promote cognitive health in the elderly.